Characterization of the Basal Ganglia Using Diffusion Tensor Imaging in Children with Self‐Injurious Behavior and Tuberous Sclerosis Complex. Issue 4 (6th May 2019) - Gipson, Tanjala T.; Poretti, Andrea; Kelley, Sarah A.; Carson, Kathryn A.; Johnston, Michael V.; Huisman, Thierry A.G.M.
ABSTRACT: BACKGROUND AND PURPOSE: Tuberous sclerosis complex (TSC) is a rare, genetic disease that is associated with multiple manifestations including epilepsy and autism. Self‐injurious behaviors (SIBs) also occur in a subset of patients. This study used diffusion tensor imaging (DTI) in children with TSC for quantitative and volumetric analysis of brain regions that have been associated with SIB in other genetic conditions. METHODS: We used DTI to compare 6 children with TSC‐associated SIB and 10 children with TSC without SIB. Atlas‐based analysis of DTI data and calculation of number of voxels; fractional anisotropy (FA); and mean, axial, and radial diffusivity were performed for multiple regions; DTI measures were summarized using medians and interquartile ranges and were compared using Wilcoxon rank sum tests and false discovery rates (FDRs). RESULTS: Analysis showed that children with TSC and SIB had reduced numbers of voxels (median) in the bilateral globus pallidus (right: 218 vs. 260, P = .008, FDR = .18; left: 222 vs. 274, P = .002, FDR = .12) and caudate nucleus (right: 712 vs. 896, P = .01, FDR = .26; left: 702 vs. 921, P = .03, FDR = .44) and reduced FA in the bilateral globus pallidus (right: .233 vs. .272, P = .003, FDR = .12; left: .223 vs. .247, P = .004, FDR = .12) and left caudate nucleus (.162 vs. .186, P = .03, FDR = .39) versus children without SIB. No other statistically significant differences were found. CONCLUSIONS: These data support a correlation between lower volumes of the globus pallidus and caudate with SIB in children with TSC.